Collection and Integration of Patent Data for Analysis and Validation of Brazilian Technical Production - (:unkn) unknown (Centro Federal de Educação Tecnológica de Minas Gerais; Instituto Brasileiro de Informação em Ciência e Tecnologia, 2023)
The main objective of this work is to present an overview of Brazilian technical production from the analysis of patents registered in national repositories such as the National Institute of Industrial Property (INPI), as well as in international repositories such as Espacenet. Initially, all the INPI patent identifiers are collected so that later, all the data of these pat ents are collected in the Espacenet repository. In this way, a large local data repository is characterized, as standing out for having consistent and structured data. This strategy makes it possible to analyze the entire dataset with the adoption of several metrics, making it possible to present a broad and unprecedented portrait of Brazilian technical production. With the dataset retrieved, it is still possible to validate other repositories or datasets, such as the curriculum base of the Lattes Platform, in which their curricula in general do not have all the information about the patents duly registered. However, it is concluded that the collection and integration of data extracted from patent documents and stored in local repositories, significantly enable patentometric analyses that could not be performed in distributed repositories.
Keywords: Patents; INPI; Lattes platform; Espacenet; Patentometry; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO